2020
DOI: 10.3390/app10103450
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Application of Virtual Reality and Internet of Things in Film and Television Production Mode

Abstract: In order to reduce some of the problems of technological restructuring and insufficient expansion in the current film and television production mode, the application of emerging technologies such as artificial intelligence (AI), virtual reality (VR), and Internet of Things (IoT) in the film and television industry is introduced in this research. First, a topical crawler tool was constructed to grab relevant texts about “AI”, “VR”, and “IoT” crossover “film and television”, and the grasping accuracy rate and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Virtual reality technology refers to the technology that is generated by using computers and allows users to observe and operate in the virtual world interactively [19]. Virtual reality technology uses 3D modeling technology and integrates with other technologies to gradually integrate into an integrated technology.…”
Section: Neural Network and Virtual Reality Technologymentioning
confidence: 99%
“…Virtual reality technology refers to the technology that is generated by using computers and allows users to observe and operate in the virtual world interactively [19]. Virtual reality technology uses 3D modeling technology and integrates with other technologies to gradually integrate into an integrated technology.…”
Section: Neural Network and Virtual Reality Technologymentioning
confidence: 99%
“…Shafer et al (2018) used VR and IoT technologies to improve the efficiency, reduce costs, and save resources in film and television production [12]. Song and Wook (2020) found that the virtual character interaction system based on the IoT technology had a higher rate of action recognition, generating a strong sense of immersion among audiences, which could realize the real-time capture and imitation of character actions [13]. Therefore, VR and IoT technology will play an essential role in film and television production; then, how to apply them in film and television production to establish new production methods and production models is of great significance for the development of China's film and television industry.…”
Section: Introductionmentioning
confidence: 99%